2021
DOI: 10.32604/iasc.2021.018914
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Web-Based Telemedicine System for Covid-19 Patients

Abstract: In the Covid-19 pandemic, people have been very concerned about the safety and are avoiding crowded places like hospitals. An online telemedicine web-based technology can help to overcome this situation. This paper presents an online telemedicine system that helps to promote collaboration between doctors, hospitals, and patients. The system allows doctors to serve patients from remote areas. The system also allows both doctors and patients to communicate through video calls or text messages. Patients using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the study he used a web-based treatment program to improve health care services, 54% of participants completed all tasks and programs to significantly improve BMI, physical, mental health, and quality of life. 27,28 The current review showed that phone and web-based telehealth have has no better effect on wound healing than standard care. This is contradictory to research conducted by Stern et al, where the probability of healing for the control period was estimated to be 35.0%, and for the intervention, period to be 53.4%.…”
Section: Discussionmentioning
confidence: 92%
“…In the study he used a web-based treatment program to improve health care services, 54% of participants completed all tasks and programs to significantly improve BMI, physical, mental health, and quality of life. 27,28 The current review showed that phone and web-based telehealth have has no better effect on wound healing than standard care. This is contradictory to research conducted by Stern et al, where the probability of healing for the control period was estimated to be 35.0%, and for the intervention, period to be 53.4%.…”
Section: Discussionmentioning
confidence: 92%
“…People can get medical treatment from their homes instead of making a visit to the doctor's office. Bangladesh is a populous country, with 100,000 people having an estimate number of only 10 doctors (Bari et al, 2021). In Bangladesh, about 10 million individuals have diabetes, and 30-40 percent of the population suffers from various types of heart disease.…”
Section: Introductionmentioning
confidence: 99%